Radiation-induced deposition of transparent conductive tin oxide coatings; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Umnov S. P. Sergey Pavlovich (Materials Science in Mechanical Engineering, 2016)
Title screen